2017
DOI: 10.1016/j.automatica.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Sequential pursuit of multiple targets under external disturbances via Zermelo–Voronoi diagrams

Abstract: We address the problem of pursuit between a collection of targets and a team of pursuers distributed in the plane subject to an environmental disturbance (e.g., wind, sea current). The objective of the pursuers is to intercept the moving targets which, however, are not affected by the presence of the flow field. We first solve the multiple-pursuers/single-target problem by assigning only one pursuer to chase the target at every instant of time, based on a Voronoi-like partition of the plane. During the pursuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For the FFMs we study, perhaps the most closely applicable networks are the Zermelo‐Voronoi diagrams (ZVD) introduced by Bakolas and Tsiotras and very recently employed by Sun and Tsiotras . Unlike a normal Voronoi diagram, a ZVD assumes that its generating points are under the influence of drift.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For the FFMs we study, perhaps the most closely applicable networks are the Zermelo‐Voronoi diagrams (ZVD) introduced by Bakolas and Tsiotras and very recently employed by Sun and Tsiotras . Unlike a normal Voronoi diagram, a ZVD assumes that its generating points are under the influence of drift.…”
Section: Related Workmentioning
confidence: 99%
“…Unlike a normal Voronoi diagram, a ZVD assumes that its generating points are under the influence of drift. Like many other applications of Voronoi diagrams generated around moving points , however, Sun and Tsiotras consider the moving points as agents and are primarily concerned with the partitions the ZVD provides as a way to decide which agent should pursue a given target. In contrast, we are interested in the edges that define the diagram as a means to construct a network within which possible ship paths can be identified that maximize the minimum distance to mines.…”
Section: Related Workmentioning
confidence: 99%
“…In this form of the game, multiple pursuers try to capture a single evader whereas the evader may win by exiting safely from the game region. A number of applications of this variant can be found in security and military applications [4][5][6] . Studied this variant of the pursuitevasion game in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous version of the game has been reported in the literature using model predictive control 11,12 , optimisation techniques 13,14 , fuzzy logic and neural network based learning approaches 13,15 . Other recently introduced methods are based on the concept of minimising the evader's Voronoi region for obtaining fast and feasible solutions in pursuit-evasion 6,16 . Sun & Tsiotras 6 have provided a pursuers' strategy based on the dynamic assignment of the pursuers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation